The Effectiveness of Education Through Audiovisuals in Increasing Mothers' Knowledge of Baby Massage to Prevent Stunting in Toddlers - Revinel, Revinel; Fatimah, Fatimah; Haque, Bunga Romadhona; Fauziah, Olivia Listy (Women, Midwives and Midwifery, 2024)
Background: The prevalence of stunting in Jakarta reached 14.80%, and stunting in North Jakarta was 18.50%, ranking second after the capital city of Jakarta. The government's target for efforts to reduce stunting nationally by 2024 is 14%. Interventions to accelerate stunting reduction are carried out in an integrated manner, to optimize growth and development, apart from nutrition, it is also necessary to provide stimulus and baby massage by mothers and families independently for their children. Purpose: To determine the effectiveness of education through audiovisuals in increasing mothers' knowledge about baby massage to prevent stunting in toddlers at the Koja District Health Center, North Jakarta. Methods: research design, one group pre-test-post test design, 62 respondents. Data collection was carried out in 3 meetings consisting of pretest, treatment, and posttest, using the Wilcoxon sign rank test. Results: Research shows Asymp. sig (2-tailed) p-value 0.0000 (P= < 0.005) z value -6.244. The research results show that education through audiovisuals is very effective in increasing mothers' knowledge about baby massage to prevent stunting in toddlers. Conclusion: Where education through audiovisual is easier to understand and mothers can teach babies to massage independently to stimulate toddlers' growth and development to prevent stunting.